Blockade of the lncRNA-DOT1L-LAMP5 axis enhances autophagy and promotes degradation of MLL fusion proteins - Tian-Qi Chen; Heng-Jing Huang; Shun-Xin Zhu; Xiao-Tong Chen; Ke-Jia Pu; Dan Wang; Yan An; Jun-Yi Lian; Yu-Meng Sun; Yue-Qin Chen; Wen-Tao Wang (Experimental Hematology & Oncology, 2024)
Abstract Background Mixed-lineage leukemia (MLL) fusion gene caused by chromosomal rearrangement is a dominant oncogenic driver in leukemia. Due to having diverse MLL rearrangements and complex characteristics, MLL leukemia treated by currently available strategies is frequently associated with a poor outcome. Therefore, there is an urgent need to identify novel therapeutic targets for hematological malignancies with MLL rearrangements. Methods qRT-PCR, western blot, and spearman correction analysis were used to validate the regulation of LAMP5-AS1 on LAMP5 expression. In vitro and in vivo experiments were conducted to assess the functional relevance of LAMP5-AS1 in MLL leukemia cell survival. We utilized chromatin isolation by RNA purification (ChIRP) assay, RNA pull-down assay, chromatin immunoprecipitation (ChIP), RNA fluorescence in situ hybridization (FISH), and immunofluorescence to elucidate the relationship among LAMP5-AS1, DOT1L, and the LAMP5 locus. Autophagy regulation by LAMP5-AS1 was evaluated through LC3B puncta, autolysosome observation via transmission electron microscopy (TEM), and mRFP-GFP-LC3 puncta in autophagic flux. Results The study shows the crucial role of LAMP5-AS1 in promoting MLL leukemia cell survival. LAMP5-AS1 acts as a novel autophagic suppressor, safeguarding MLL fusion proteins from autophagic degradation. Knocking down LAMP5-AS1 significantly induced apoptosis in MLL leukemia cell lines and primary cells and extended the survival of mice in vivo. Mechanistically, LAMP5-AS1 recruits the H3K79 histone methyltransferase DOT1L to LAMP5 locus, directly activating LAMP5 expression. Importantly, blockade of LAMP5-AS1-LAMP5 axis can represses MLL fusion proteins by enhancing their degradation. Conclusions The findings underscore the significance of LAMP5-AS1 in MLL leukemia progression through the regulation of the autophagy pathway. Additionally, this study unveils the novel lncRNA-DOT1L-LAMP5 axis as promising therapeutic targets for degrading MLL fusion proteins.